Graphene and Carbon Nanotubes for Advanced Lithium Ion Batteries - Figerez, Stelbin Peter; Prasanth, Raghavan; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
This title covers the fundamentals of carbon nanomaterials in a logical and clear manner to make concepts accessible to researchers from different disciplines. It summarizes in a comprehensive manner recent technological and scientific accomplishments in the area of carbon nanomaterials and their application in lithium ion batteries The book also addresses all the components anodes, cathodes and electrolytes of lithium ion battery and discusses the technology of lithium ion batteries that can safely operate at high temperature.
1. Carbon Nanomaterials Are Resolving the Challenges and Issues of Future Lithium Ion Batteries. 2. Carbon Nanotube and Its Composites as Anodes for Lithium Ion Batteries. 3. Carbon Nanotube and Its Composites as Cathodes for Lithium Ion Batteries. 4. Carbon Nanotube/Polymer Nanocomposite Electrolytes for Lithium Ion Batteries. 5. Graphene and Its Composites as Anode for Lithium Ion Batteries. 6. Graphene and Its Composites as Cathodes for Lithium Ion Batteries. 7. Graphene/Polymer Nanocomposite Electrolyte for Lithium Ion Batteries.
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Electronics / General; TECHNOLOGY & ENGINEERING / Material Science; anode; cathodes; electrochemical energy storage and conversion; electrolytes; nanomaterials applications in electrochemistry; polymer nanocomposites; Lithium ion batteries -- Materials; Graphene; Carbon nanotubes; Electronic books